Development of a fabric-based soft hand exoskeleton for rehabilitation and assistance - Maldonado Mejía, Juan Camilo (Maestría en Ingeniería Electrónica, 2022)
According to the World Health Organization (WHO), stroke is the third leading cause of disability and the second leading cause of death worldwide, mainly affecting lower-middle-income countries. The upper limb, specifically the hand, is one of the most common motor disabilities following a stroke. The hand plays a vital role in performing activities of daily living (ADLs), so hand rehabilitation is essential. With technological development in recent years, soft robotics has emerged as a possible solution to provide physical and cognitive assistance during rehabilitation. This master’s thesis presents the development of two versions of a replicable hand exoskeleton for hand rehabilitation and assistance in ADLs based on soft robotics for stroke survivors, the ExHand Exoskeleton. The device is evaluated through standard functionality and usability tests on ten healthy subjects. The results demonstrate that the device satisfies the requirements of a hand exoskeleton for rehabilitation and assistance with a glove weight of 137 g and total system weight of 971 g, as well as its actuators perform a distal force of 9.18 ± 1.16 N, sufficient to grasp different objects associated with ADLs. Likewise, the person using the device can perform different daily living activities, such as writing and eating. In addition, the ExHand Exoskeleton can perform eight types of grasping with 24 objects of different shapes, sizes, textures, weights, and stiffness with 80.80% similarity to a healthy user. Also, the user satisfaction questionnaire results indicated a positive mean score of 4.27 ± 0.34 on a Likert scale ranging from 1 to 5. Finally, two surveys were conducted to evaluate the acceptance and intention of use by clinicians, showing that the device is a valuable and easy-to-use tool to support neurological patients.

Según la Organización Mundial de la Salud (OMS), el ictus es la tercera causa de discapacidad y la segunda causa de muerte en todo el mundo, afectando principalmente a los países de ingresos medios-bajos. El miembro superior, concretamente la mano, es uno de los movimientos motores más comunes. discapacidades después de un accidente cerebrovascular. La mano juega un papel vital en la realización de actividades de la vida diaria. (AVD), por lo que la rehabilitación de la mano es fundamental. Con el desarrollo tecnológico en los últimos años, la robótica blanda ha surgido como una posible solución para brindar asistencia física y cognitiva durante la rehabilitación. Esta tesis de maestría presenta el desarrollo de dos versiones de un exoesqueleto de mano replicable para rehabilitación de manos y asistencia en AVD basado en robótica blanda para supervivientes de accidentes cerebrovasculares, ExHand Exoskeleton. El dispositivo se evalúa a través de Pruebas estándar de funcionalidad y usabilidad en diez sujetos sanos. Los resultados demuestran que el dispositivo cumple los requisitos de un exoesqueleto de mano para rehabilitación y asistencia con un peso de guante de 137 g y un peso total del sistema de 971 g, así como sus actuadores realizar una fuerza distal de 9,18 ± 1,16 N, suficiente para agarrar diferentes objetos asociados con actividades de la vida diaria. Asimismo, la persona que utiliza el dispositivo puede realizar diferentes tareas diarias actividades de la vida, como escribir y comer. Además, el exoesqueleto ExHand puede realizar ocho tipos de agarre con 24 objetos de diferentes formas, tamaños, texturas, pesos y rigidez con un 80,80% de similitud con un usuario sano. Asimismo, el cuestionario de satisfacción del usuario Los resultados indicaron una puntuación media positiva de 4,27 ± 0,34 en una escala de Likert que va de 1 a 5. Finalmente, se realizaron dos encuestas para evaluar la aceptación e intención de uso por médicos, lo que demuestra que el dispositivo es una herramienta valiosa y fácil de usar para apoyar neurológico pacientes
Keywords: Exoesqueleto de mano; Robótica; Rehabilitación; Exoesqueleto de mano; Hand Exoskeleton; Robótica; Robotics; Rehabilitación; Rehabilitation